Enhancing Students' Learning Engagement Through Slido-Based Gamification In High School English Classes - Merina, Donata Risa; Nurwahidin, Muhammad; Firdaus, Rangga (UNDIKMA, 2025)
This study investigates the impact of using the Slido platform as a gamification tool on student engagement in English language learning at the secondary school level. The research is motivated by the challenges faced in enhancing student engagement through traditional teaching methods, particularly in Indonesia, where technology integration in education remains relatively low. Gamification, which incorporates games such as rewards, points, and challenges, has significantly boosted student participation and motivation. The study uses a quantitative experimental design with two groups: an experimental group that uses Slido for interactive activities such as quizzes, polls, and Q&A sessions, and a control group that follows conventional teaching methods. Data collected from pre-tests, post-tests, and student engagement surveys indicate a substantial increase in engagement among students who used Slido, with the experimental group showing a 29.8% improvement in engagement scores compared to a 6.8% improvement in the control group. These results suggest that Slido's gamified features, by fostering real-time interaction and feedback, effectively enhance student involvement and motivation. The findings offer valuable insights for educators on integrating gamification tools like Slido to improve student participation and create a more dynamic and enjoyable learning environment.